Prognostic value of antibodies to Merkel cell polyomavirus T antigens and VP1 protein in patients with Merkel cell carcinoma. (1st April 2016) - Samimi, M.; Molet, L.; Fleury, M.; Laude, H.; Carlotti, A.; Gardair, C.; Baudin, M.; Gouguet, L.; Maubec, E.; Avenel‐Audran, M.; Esteve, E.; Wierzbicka‐Hainaut, E.; et al.
Summary: Background: Merkel cell polyomavirus (MCPyV) is the main aetiological agent of Merkel cell carcinoma (MCC). Serum antibodies against the major MCPyV capsid protein (VP1) are detected in the general population, whereas antibodies against MCPyV oncoproteins (T antigens) have been reported specifically in patients with MCC. Objectives: The primary aim was to assess whether detection of serum antibodies against MCPyV proteins at baseline was associated with disease outcome in patients with MCC. The secondary aim was to establish whether evolution of these antibodies during follow‐up was associated with the course of the disease. Methods: Serum T‐antigen and VP1 antibodies were assessed by enzyme‐linked immunosorbent assay using recombinant proteins in a cohort of 143 patients with MCC, including 84 patients with serum samples available at baseline. Results: Low titres of VP1 antibodies at baseline (< 10 000) were significantly and independently associated with increased risk of recurrence [hazard ratio (HR) 2·71, 95% confidence interval (CI) 1·13–6·53, P = 0·026] and death (HR 3·74, 95% CI 1·53–9·18, P = 0·004), whereas T‐antigen antibodies were not found to be associated with outcome. VP1 antibodies did not differ between patients in remission and those with recurrence or progression during follow‐up. However, T‐antigen antibodies were more frequently detected in patients with recurrence or progression at 12 months ( P = 0·020) and 24 months ( P = 0·016) after diagnosis. Conclusions: VP1 antibodies constitute a prognostic marker at baseline, whereas T‐antigen antibodies constitute a marker of disease recurrence or progression if detected > 12 months after diagnosis.